Would Agricultural Credit Sustain Agricultural Output in Nigeria? An Empirical Perspective: Array - Ebere, Chidinma Edith; Oresanwo, Adeniyi Marcus; Omogboye, Michael Abayomi; Aderemi, Timothy Ayomitunde (The Journal of Accounting and Management, 2021)
This study examines the sustainability of agricultural output through agricultural credit in Nigeria. Secondary data from the Central Bank of Nigeria Statistical Bulletin was utilized from 1981-2019. Cointegration, DOLS and Granger Causality were employed in analyzing the objective of the study. Moreover, the study results found that credit disbursed to the agricultural sector has a significant positive impact on agricultural output in Nigeria. However, agricultural expenditure has an insignificant direct linkage with output from agriculture in Nigeria. Also, there exists a unidirectional causality which runs from agricultural credit to agricultural expenditure. Likewise, a one-way feedback effect runs from agricultural output to agricultural expenditure in Nigeria. This research is the first empirical study that tests the sustainability of agricultural output through agricultural credit in Nigeria. Therefore, the policymakers in the country are advised to be committed to financing of the agricultural sector because it has the capacity to sustain agricultural output and as such food security and zero hunger would be guaranteed in the country. Also, there should be an increase in the allocation of the national budget to the agricultural sector in Nigeria.